Coding the negative emotions of family members and patients among the high‐risk preoperative conversations with the Chinese version of VR‐CoDES - Liru Qian; Xinchun Liu; Meng Yin; Ya Zhao; Bingyu Tie; Qingyan Wang; Yi Zhang; Siyang Yuan (Health Expectations, 2022)
Abstract Background Little is known about family members' and patients' expression of negative emotions among high‐risk preoperative conversations. Objectives This study aimed to identify the occurrence and patterns of the negative emotions of family members and patients in preoperative conversations, to investigate the conversation themes and to explore the correlation between the negative emotions and the conversation themes. Methods A retrospective study was conducted using the Chinese version of Verona Coding Definitions of Emotional Sequences (VR‐CoDES‐C) to code 297 conversations on high‐risk procedures. Inductive content analysis was used to analyse the topics in which negative emotions nested. The χ2 Test was used to test the association between the cues and the conversation themes. Results The occurrence rate of family members' and patients' negative emotions was very high (85.9%), much higher when compared to most conversations under other medical settings. The negative emotions were mainly expressed by cues (96.4%), and cue‐b (67.4%) was the most frequent category. Cues and concerns were mostly elicited by family members and patients (71.6%). Negative emotions were observed among seven themes, in which ‘Psychological stress relating to illness severity, family's care and financial burden’ (30.3%) ranked the top. Cue‐b, cue‐c and cue‐d had a significant correlation (p < .001) with certain themes. Conclusions Family members and patients conveyed significantly more negative emotions in the high‐risk preoperative conversations than in other medical communications. Certain categories of cues were induced by specific emotional conversation contents. Patient Contribution Family members and patients contributed to data.